Changes in body composition, hormonal status, and physical fitness in 11-, 13-, and 15- year old finnish regional youth soccer players during a two-year follow-up - Vänttinen, T.; Blomqvist, M.; Nyman, K.; Häkinnen, K. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the changes in body composition, hormonal status, and physical fitness in 10.8 ± 0.3-year-old (n = 13), 12.7 ± 0.2-year-old (n = 14), and 14.7 ± 0.3-year-old (n = 12) Finnish regional youth soccer players during a 2-year monitoring period and to compare physical fitness characteristics of soccer players with those of age-matched controls (10.7 ± 0.3 years, n = 13; 14.7 ± 0.3 years, n = 10) not participating in soccer. Body composition was measured in terms of height, weight, muscle mass, percentage of body fat, and lean body weight of trunk, legs, and arms. Hormonal status was monitored by concentrations of serum testosterone and cortisol. Physical fitness was measured in terms of sprinting speed, agility, isometric maximal strength (leg extensors, abdominal, back, grip), explosive strength, and endurance. Age-related development was detected in all other measured variables except in the percentage of body fat. The results showed that the physical fitness of regional soccer players was better than that of the control groups in all age groups, especially in cardiovascular endurance (p < 0.01-0.001) and in agility (p < 0.01-0.001). In conclusion, playing in a regional level soccer team seems to provide training adaptation, which is beyond normal development and which in all likelihood leads to positive health effects over a prolonged period of time.